A flexible pressure-sensitive color-changing anticorrosive primer, preparation method and application thereof, and an intelligent threaded fastener with visual tightening degree
By developing a flexible pressure-sensitive color-changing anticorrosion primer, the problem of anticorrosion coatings prone to cracking under vibration and deformation in the prior art is solved, and effective corrosion and tightening of rivets, joints and key parts of fatigue is achieved. Rapid inspection reduces corrosion risks and detection costs.
Patent Information
- Application Number
- CN202310658562.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-06
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-06-06
AI Technical Summary
In the prior art, anticorrosion coatings used in rivets, joints and key parts of fatigue are rigid, and are prone to microcracking or cracking under vibration and deformation, losing their protective effect, resulting in crevice corrosion or galvanic corrosion, which may cause serious ACCIDENT.
A flexible pressure-sensitive color-changing anticorrosion primer was developed, using traditional air spraying method, the coating application period can reach 6 hours and the surface drying time is 40 minutes, and it has excellent comprehensive mechanical properties and tensile fatigue resistance. This primer is used in rivets, joints and key parts of fatigue, which can effectively prevent corrosion and verify the tightness of threaded fasteners and connections through color changes.
This flexible pressure-sensitive color-changing anti-corrosion primer can effectively prevent corrosion in rivets, joints and fatigue-related key parts, extend the service life of the material, and quickly check the tightening degree through color changes, reducing maintenance time and manual inspection costs.
Smart Images

Figure CN116855163B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a flexible pressure-sensitive color-changing anti-corrosion primer, a preparation method and application thereof, and an intelligent threaded fastener with a visible tightening degree. Background Art
[0002] With the development of lightweight materials, lightweight materials such as aluminum alloys and composite materials are more widely used. At present, the combination of different materials mostly relies on rivets, screws and other methods, and most of the anti-corrosion measures for these parts are to spray anti-corrosion coatings together with the main body. In actual application, the coatings used for rivets, joints and fatigue-critical parts will be subjected to large loads during high-speed use. Due to the effects of vibration and deformation, the rigid coating is prone to microcracks or cracks in the above-mentioned parts, thereby losing the protective effect on the metal matrix, and then causing crevice corrosion or galvanic corrosion, destroying the material joints. The development of crevice corrosion is hidden and sudden, and the initial corrosion has a long incubation period. After the corrosion level reaches a certain critical level, the rivets or joints will be damaged during high-speed use, causing serious accidents.
[0003] In the 1990s, the U.S. military formulated the federal standard "TT-P-2760 High Solid Elastic Polyurethane Primer", which is a polyurethane elastic primer specifically used for rivets and seams and for use with high-flexibility skin topcoats. The standard requires not only good physical and mechanical properties of the coating, but also good anti-corrosion protection. For example, DeSoto developed a single-component elastic moisture-curing aircraft polyurethane primer with the brand name Koroflex. Its coating can bend with the vibration of the aircraft to prevent cracking of the coating at rivets and other high-stress locations, and even if the topcoat is damaged, the primer layer can continue to protect the substrate. This primer can also be used on composite materials and rubber, and has excellent adhesion to the topcoat. SHERWIN-WILLIAMS, an aviation coating supplier, has produced a high-performance two-component chrome-free elastic epoxy primer with the brand name CM0483790, which has high flexibility, good media resistance and excellent adhesion. Bayer MaterialScience of Germany has developed an aspartic acid polyester urea coating with good elasticity and excellent weather resistance. This coating is used on ICE high-speed trains, but it is not suitable for areas with a wide temperature range. At present, there are few flexible primers specially developed for rivets, joints and key fatigue parts in China. Therefore, it is very necessary to prepare a flexible anti-corrosion primer for rivets, joints and key fatigue parts. At the same time, it is also very necessary to invent a simple and easy-to-industrial method to prepare intelligent threaded fasteners with visual tightening degree to reduce inspection costs. Summary of the invention
[0004] In order to solve the problems in the prior art, the present invention provides a flexible pressure-sensitive color-changing anti-corrosion primer, a preparation method and application, and an intelligent threaded fastener with visual tightness. The flexible pressure-sensitive color-changing anti-corrosion primer can be sprayed by traditional air spraying, and the coating application period can reach 6 hours, the surface drying time can reach 40 minutes, and the construction is convenient. It has excellent comprehensive mechanical properties and good tensile fatigue resistance. It can be used for rivets, joints, and fatigue-critical parts, and can effectively prevent the occurrence of corrosion. More importantly, the coating has a pressure-induced color-changing function, and the tightness of threaded fasteners and joints can be effectively checked through color changes, reducing maintenance time and avoiding losses caused by loosening of threaded fasteners.
[0005] One of the purposes of the present invention is to provide a flexible pressure-sensitive color-changing anti-corrosion primer, comprising component A and component B; the component A comprises a flexible resin, a pressure-induced color-changing indicator, ultrafine talcum powder, nano-aluminum oxide and a wetting dispersant; the component B comprises a flexible curing agent and an adhesion promoter.
[0006] In a preferred embodiment of the present invention,
[0007] Each component in the A component is calculated based on 100 parts by weight of the flexible resin.
[0008] 100 to 180 parts by weight of a piezochromic indicator; preferably 120 to 170 parts by weight; more preferably 140 to 170 parts by weight;
[0009] Ultrafine talc powder 20 to 80 parts by weight; preferably 30 to 50 parts by weight; more preferably 35 to 45 parts by weight;
[0010] 30 to 80 parts by weight of nano-aluminum oxide; preferably 30 to 50 parts by weight; more preferably 35 to 40 parts by weight;
[0011] Wetting and dispersing agent 2 to 5 parts by weight; preferably 2 to 4 parts by weight; more preferably 3 to 4 parts by weight;
[0012] The components in the B component are calculated based on 100 parts by weight of the flexible curing agent.
[0013] Adhesion promoter 0-10 parts by weight; preferably 2-10 parts by weight; more preferably 4-6 parts by weight;
[0014] The usage ratio of component A to component B is (4-12):1, preferably (4-10):1, and more preferably (5-10):1.
[0015] In a preferred embodiment of the present invention,
[0016] The flexible resin is selected from at least one of a flexible epoxy-modified acrylic resin and a flexible polyisocyanate prepolymer resin; preferably,
[0017] The flexible epoxy-modified acrylic resin is selected from conventional flexible epoxy-modified acrylic resins in the prior art, and in the present invention, preferably selected from one or more of A-8200 resin of Suzhou Qingtian New Materials Co., Ltd., TC-101B and F221 resin of Green Union Chemical Technology Co., Ltd.; and / or,
[0018] The flexible polyisocyanate prepolymer resin can be obtained from commercial sources or prepared by any method in the prior art. In the present invention, it is preferably prepared by a preparation method comprising the following steps:
[0019] Step 1: reacting isocyanate, catalyst and part of solvent A to obtain material 1;
[0020] Step 2: Add a stabilizer and a cross-linking agent to material 1 to react to obtain material 2;
[0021] Step 3: Adding oligomer polyol to material 2 to react to obtain material 3;
[0022] Step 4: adding an anticoagulant to material 3 to react, and after the reaction is completed, adding the remaining solvent A to obtain a flexible polyisocyanate prepolymer resin.
[0023] In a preferred embodiment of the present invention,
[0024] The isocyanate is selected from one or more of isophorone diisocyanate, hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, and p-phenylene diisocyanate, preferably isophorone diisocyanate and / or p-phenylene diisocyanate, with the main component being ≥99%; and / or,
[0025] The catalyst is selected from one or more of triethylamine and dioctyltin dilaurate; and / or,
[0026] The stabilizer is selected from conventional stabilizers in the art, preferably one or more of Stabaxol-1 and Stabaxol-P stabilizers; and / or,
[0027] The oligomer polyol is selected from one or more of polycaprolactone diol, polyether polyol and polybutadiene polyol; and / or,
[0028] The cross-linking agent is selected from conventional cross-linking agents in the art, preferably one or more selected from trimethylolpropane (TMP), 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA), dimethylthiotoluene diamine (DMTDA); and / or,
[0029] The anticoagulant is selected from one or more of benzoyl chloride and phosphoric acid; and / or,
[0030] The solvent A is selected from one or more of butyl acetate, ethyl acetate, and propylene glycol methyl ether acetate, and has a water content of ≤0.2%.
[0031] The method for preparing the flexible polyisocyanate prepolymer resin of the present invention can adopt the following specific steps:
[0032] Step 1: Add 30-45 parts by weight of isocyanate, 0.01-0.05 parts by weight of catalyst and 15-30 parts by weight of solvent A into a reaction kettle, introduce nitrogen protection, stir at 20-30° C. for 10-20 minutes to mix the materials evenly, then heat to 60-65° C. and react for 10-20 minutes to obtain material 1.
[0033] Step 2: Add 0.1 to 1.0 parts by weight of stabilizer to material 1, heat to 70 to 80°C, slowly add 1.0 to 1.5 parts by weight of cross-linking agent under stirring, and react at 85 to 95°C for 1 to 1.5 hours to obtain material 2.
[0034] Step 3: Slowly add 40 to 55 parts by weight of oligomer polyol to material 2 at 70 to 80° C. with stirring, react at 85 to 95° C. for 2 to 2.5 hours, and then cool to 40 to 50° C. to obtain material 3.
[0035] Step 4: Slowly add 0.01 to 0.05 parts by weight of anticoagulant to material 3 at 40 to 50° C. with stirring. After the addition, keep the reaction at 40 to 50° C. for 1 to 1.5 hours. After the reaction is completed, add 0 to 30 parts by weight of solvent A, cool the temperature to below 40° C., discharge the material, and seal and package to obtain the flexible polyisocyanate prepolymer resin.
[0036] In a preferred embodiment of the present invention,
[0037] The ultrafine talc powder is selected from conventional talc powder in the prior art, with a fineness of 500-2000 mesh, preferably 1250-2000 mesh, more preferably 1250-1500 mesh, and in the present invention, preferably selected from one or more of Guangxi osmanthus talc powder and Qingdao white pigeon talc powder; and / or,
[0038] The nano aluminum oxide is selected from conventional nano aluminum oxide in the prior art, with a particle size of 5 to 500 nm, preferably 10 to 100 nm, more preferably 20 to 80 nm, preferably at least one of α-phase and γ-phase nano aluminum oxides, more preferably one or more of α-phase nano aluminum oxide of Baoket New Materials Co., Ltd. and α-phase nano aluminum oxide of Hengna New Materials Co., Ltd.; and / or,
[0039] The piezochromic indicator is selected from conventional indicators in the prior art, and in the present invention, one or more of 2-phenylamino-3-methyl-6-dibutylaminofluoran of Shanghai Ruinian Fine Chemical Co., Ltd. and 7-diethylamino-3-[4'-(trifluoromethyl)benzoyl]methylcoumarin of Sichuan Hengcheng Zhiyuan Biotechnology Co., Ltd. are preferred; and / or,
[0040] The wetting and dispersing agent is selected from conventional dispersants in the prior art, and in the present invention, is preferably selected from one or more of AFCONA4015, BYK103, and RD9125; and / or,
[0041] The flexible curing agent is selected from conventional curing agents in the prior art, preferably one or more of polyurea curing agents and polyisocyanate curing agents in the present invention, more preferably one or more of GB805A-100 and E402-90T; and / or,
[0042] The adhesion promoter is selected from conventional promoters in the prior art, and in the present invention, preferably one or more of amino-modified silicon compound adhesion promoters, and more preferably one or more of Deqian 1121 and Jessica's JSC-1120.
[0043] The A component may also be added with conventional fillers or additives in the art, such as any one of fumed silica, leveling agent, defoamer, solvent B, etc., and the amount used is also conventional. In the present invention, each component is preferably calculated based on 100 parts by weight of the flexible resin.
[0044] 1.5 to 5 parts by weight of fumed silica; preferably 2 to 4 parts by weight;
[0045] 1 to 5 parts by weight of leveling agent; preferably 2 to 4 parts by weight;
[0046] 1 to 5 parts by weight of defoamer; preferably 2 to 3 parts by weight;
[0047] Solvent B 30 to 80 parts by weight; preferably 40 to 60 parts by weight.
[0048] The fumed silica is selected from conventional fumed silica in the prior art, preferably selected from fumed silica with a specific surface area of 50-300 m 2 / g of hydrophobic fumed silica, more preferably one or more of HB-151 of Hubei Huifu Nano Technology Co., Ltd. and SJ-301 of Weifang Sanjia Chemical Co., Ltd.; the fumed silica mainly plays an anti-settling role; and / or,
[0049] The leveling agent is selected from conventional leveling agents in the prior art, and in the present invention, is preferably selected from one or more of BYK-378 and Levaslip 466; and / or,
[0050] The defoamer is selected from conventional defoamers in the prior art, and in the present invention, is preferably selected from one or more of BYK065 and AFCONA2020; and / or,
[0051] The solvent B is selected from conventional solvents in the prior art, and in the present invention, is preferably selected from one or more of ethyl acetate, butyl acetate, and propylene glycol methyl ether acetate, and has a water content of ≤0.2%.
[0052] The second object of the present invention is to provide a method for preparing the flexible pressure-sensitive color-changing anticorrosive primer of one of the objects of the present invention, comprising:
[0053] Firstly, component A and component B are mixed separately, and then component A and component B are mixed to obtain the flexible pressure-sensitive color-changing anticorrosive primer.
[0054] The present invention can adopt the following specific technical solutions:
[0055] (1) In a container, a flexible resin, ultrafine talc, nano aluminum oxide, a wetting dispersant, an optional fumed silica, an optional solvent B, an optional leveling agent, and an optional defoaming agent are stirred in sequence for 0.5 to 1.5 hours, ground and dispersed with a sand mill until the fineness is ≤40 μm, and then a pressure-induced color-changing indicator is added, and the mixture is stirred at a high speed in a sealed container for 0.5 to 1.5 hours, the material is filtered out, and the flexible pressure-sensitive color-changing anticorrosive primer component A is obtained by sealing and packaging;
[0056] (2) Stirring the flexible curing agent and the adhesion promoter in a container for 0.5 to 1 hour, filtering the material, and sealing and packaging to obtain a flexible pressure-sensitive color-changing anticorrosive primer component B;
[0057] (3) Component A and component B are mixed to obtain the flexible pressure-sensitive color-changing anti-corrosion primer.
[0058] The third object of the present invention is to provide a flexible pressure-sensitive color-changing anti-corrosion primer of one of the objects of the present invention or a flexible pressure-sensitive color-changing anti-corrosion primer prepared by the method of the second object of the present invention for use in threaded fasteners, rivets, joints and fatigue-critical parts.
[0059] A fourth object of the present invention is to provide an intelligent threaded fastener with visible tightening degree, wherein the fastener is a screw, or includes a bolt and a nut and optionally a gasket, and the outer layer of the screw or bolt is coated with the flexible pressure-sensitive color-changing anti-corrosion primer of one of the objects of the present invention or the flexible pressure-sensitive color-changing anti-corrosion primer prepared by the method of the second object of the present invention.
[0060] In a preferred embodiment of the present invention,
[0061] The bolt comprises a bolt head and a bolt column, wherein the bolt head is located at the upper part of the bolt column, and an annular groove is provided on the end face of the bolt head, and the center of the annular groove is located on the axis of the bolt column; the annular groove is used to fill the flexible pressure-sensitive color-changing anti-corrosion primer to display the degree of tightening; preferably,
[0062] The annular groove penetrates into the bolt column part, and the depth of the annular groove penetrating into the bolt column part is preferably 1 / 8 to 1 / 4 of the length of the bolt column; and / or, the width of the annular groove is 1 to 2 mm; and / or,
[0063] The annular groove is filled with a coating of the flexible pressure-sensitive color-changing anti-corrosion primer; and / or,
[0064] The outer diameter of the annular groove is smaller than the diameter of the bolt column, preferably 0.8-3 mm smaller than the diameter of the bolt column; and / or,
[0065] The ratio of the inner diameter of the annular groove to the diameter of the bolt column is 0.25-0.5.
[0066] In a preferred embodiment of the present invention,
[0067] The screw comprises a screw head and a screw rod, wherein the screw head is located at the upper part of the screw rod, an annular groove is provided on the end surface of the screw head, and the center of the annular groove is located on the axis of the screw rod; preferably,
[0068] The annular groove penetrates into the screw part, and the depth of the annular groove into the screw part is preferably 1 / 8 to 1 / 4 of the length of the screw; and / or, the width of the annular groove is 1 to 2 mm; and / or,
[0069] The annular groove is filled with a coating of the flexible pressure-sensitive color-changing anti-corrosion primer; and / or,
[0070] The outer diameter of the annular groove is smaller than the diameter of the screw, preferably 0.8-3 mm smaller than the diameter of the screw; and / or,
[0071] The ratio of the inner diameter of the annular groove to the diameter of the screw is 0.25 to 0.5.
[0072] The material of the threaded fastener can be selected from conventional metals in the art, preferably aluminum alloy.
[0073] The bolt can be obtained by cutting a circle on the end face of the bolt head to form an annular groove, from a conventional bolt including a bolt head and a bolt column in the prior art.
[0074] The screw can be obtained by cutting a circle on the end face of the screw head to form an annular groove, from a conventional screw including a screw head and a screw rod in the prior art.
[0075] In a preferred embodiment of the present invention,
[0076] The method for preparing the threaded fastener with visible tightening degree comprises the steps of spraying the flexible pressure-sensitive color-changing anti-corrosion primer on the surface of the threaded fastener and then curing the primer.
[0077] The present invention can adopt the following specific technical solutions:
[0078] The method for preparing the intelligent threaded fastener with visual tightening degree preferably comprises the following steps:
[0079] 1) Cut the end face of the bolt head around the center point to form an annular groove, then soak the treated bolt in xylene for 4 to 6 hours, take it out and dry it.
[0080] 2) Spray the bolts treated in step 1 with a flexible pressure-sensitive color-changing anti-corrosion primer, and fill the annular groove with the flexible pressure-sensitive color-changing anti-corrosion primer until it is completely cured.
[0081] The nuts and / or washers matched with the bolts in the present invention are also preferably immersed in xylene for 4 to 6 hours, taken out and dried, and then sprayed with a flexible pressure-sensitive color-changing anticorrosive primer and used after being completely cured.
[0082] The nut and the washer can be any nut and washer in the prior art, as long as they can match the size of the bolt of the present invention.
[0083] The present invention applies a certain pressure to the flexible pressure-sensitive color-changing anti-corrosion primer in the groove by tightening the screws or bolts. When the pressure is sufficient, the paint changes color, indicating that the tightening degree of the screws or bolts is sufficient.
[0084] The beneficial effects of the present invention are as follows:
[0085] The flexible pressure-sensitive color-changing anticorrosive primer of the present invention has a simple preparation method, a good coating application period, and can be applied to traditional air spraying. The coating has good pressure-sensitive color change, corrosion resistance and environmental adaptability, and can well solve the problem of micro-corrosion of threaded fasteners, rivets, joints and fatigue key parts. By observing the color change of the threaded fasteners with visible tightness (if the coating does not change color, it means that the tightness is low, if the coating changes color, it means that a certain pressure is reached and it is basically tight), it can be quickly and conveniently found whether the threaded fasteners meet the tightness requirements, thereby reducing the losses caused by tightness problems and reducing the cost of manual inspection. BRIEF DESCRIPTION OF THE DRAWINGS
[0086] Figure 1 It is a schematic top view of the structure of the bolt in the intelligent threaded fastener with visual tightening degree, wherein 1 is the bolt column, 2 is the annular groove, and 3 is the bolt head;
[0087] Figure 2 The diagram is a schematic front view of the structure of a bolt in a smart threaded fastener with visual tightening degree, wherein 1 is the bolt column, 2 is the annular groove, and 3 is the bolt head. DETAILED DESCRIPTION
[0088] The present invention is described in detail below in conjunction with specific embodiments and drawings. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.
[0089] The raw materials used in the examples are all conventional commercially available raw materials.
[0090] Example 1
[0091] The preparation method of the flexible polyisocyanate prepolymer resin in this embodiment comprises the following steps:
[0092] Step 1: Add 30 parts by weight of hexamethylene diisocyanate, 0.01 parts by weight of triethylamine and 15 parts by weight of butyl acetate into a reaction kettle, introduce nitrogen protection, stir at 150 r / min at 25°C for 20 minutes to mix the materials evenly, then heat to 60°C and react for 15 minutes to obtain material 1.
[0093] Step 2: Add 0.12 parts by weight of Stabaxol-1 to material 1, heat to 78°C, slowly add 1.2 parts by weight of TMP under stirring at 180 r / min, and react at 85°C for 1.5 hours to obtain material 2.
[0094] Step 3: Slowly add 45 parts by weight of polycaprolactone diol PCL2053 produced by Wuhan Shuer Biotechnology Co., Ltd. to material 2 at 78°C and stirring at 180 r / min, react at 85°C for 2.5 hours, then cool to 45°C to obtain material 3.
[0095] Step 4: Slowly add 0.02 parts by weight of benzoyl chloride to material 3 at 45°C and stirring at 150 r / min. After the addition, keep the reaction at 40°C for 1.5 hours. After the reaction is completed, add 8 parts by weight of butyl acetate, cool to below 40°C, discharge the material, and seal and package to obtain a flexible polyisocyanate prepolymer resin.
[0096] The formula composition and preparation process of the flexible pressure-sensitive color-changing anticorrosive primer in this embodiment are as follows:
[0097] (1) 45 parts by weight of butyl acetate solvent, 100 parts by weight of the above-obtained flexible polyisocyanate prepolymer resin, 35 parts by weight of Guangxi Guihua 1250 mesh ultrafine talc powder, 40 parts by weight of α-phase nano-alumina (model PAT-05A) of Baoket New Materials Co., Ltd., 3.5 parts by weight of fumed silica SJ-301, 2.5 parts by weight of BYK-378 leveling agent, 2.5 parts by weight of BYK065 defoamer, and 3.5 parts by weight of AFCONA4015 wetting and dispersing agent were added to a container in sequence and stirred for 1 hour, and ground and dispersed with a sand mill until the fineness was ≤40 μm, and then 150 parts by weight of 2-phenylamino-3-methyl-6-dibutylaminofluorane was added, and the mixture was stirred at high speed in a closed manner for 0.5 hour, filtered out, and sealed and packaged to obtain component A; component A had a solid content of 63% and a fineness of 35 μm;
[0098] (2) In a container, 100 parts by weight of GB805A-100 flexible curing agent and 5.5 parts by weight of Deqian 1121 adhesion promoter were stirred for 0.5 h, filtered, and sealed to obtain component B;
[0099] (3) The component A and the component B prepared above were mixed in a weight ratio of A:B=80:10 to prepare a coating material. The coating thickness obtained after coating for performance testing was 40 to 60 μm.
[0100] The preparation method of the intelligent threaded fastener with visual tightening degree is as follows:
[0101] 1) A circle is cut around the center point of the bolt head end face of an external hexagonal aluminum alloy bolt (total length 3 cm, bolt head thickness 4 mm, bolt diameter 6 mm, hexagonal opposite side length 8 mm) to form an annular groove with a depth of 8 mm, a width of 1 mm, and an inner diameter of 2 mm. Then, the processed bolts and the matching nuts and gaskets are immersed in xylene for 5 hours, taken out and dried.
[0102] 2) First, the component A and the component B of the flexible pressure-sensitive color-changing anti-corrosion primer of the above-mentioned embodiment 1 are mixed according to the described usage ratio (80:10) to obtain the flexible pressure-sensitive color-changing anti-corrosion primer, and then the bolts, nuts and gaskets treated in step 1) are sprayed with the flexible pressure-sensitive color-changing anti-corrosion primer respectively, and the coating is made to fill the annular groove, and the coating is completely cured to obtain a smart threaded fastener with a visible tightness.
[0103] Example 2
[0104] The preparation method of the flexible polyisocyanate prepolymer resin in this embodiment comprises the following steps:
[0105] Step 1: Add 38 parts by weight of p-phenylene diisocyanate, 0.01 parts by weight of dioctyltin dilaurate and 18 parts by weight of ethyl acetate into a reaction kettle, introduce nitrogen protection, stir at 150 r / min at 25°C for 20 minutes to mix the materials evenly, then heat to 63°C and react for 15 minutes to obtain material 1.
[0106] Step 2: Add 0.12 parts by weight of Stabaxol-1 to material 1, heat to 78°C, slowly add 1.0 parts by weight of TMP under stirring at 180 r / min, and react at 85°C for 1.5 hours to obtain material 2.
[0107] Step 3: Slowly add 43 parts by weight of polycaprolactone diol PCL2053 produced by Wuhan Shuer Biotechnology Co., Ltd. to material 2 at 78°C and stirring at 180 r / min, react at 85°C for 2.5 hours, then cool to 45°C to obtain material 3.
[0108] Step 4: Slowly add 0.01 parts by weight of benzoyl chloride to material 3 at 45°C and stirring at 150 r / min. After the addition, keep the reaction at 45°C for 1.5 hours. After the reaction is completed, add 10 parts by weight of ethyl acetate, cool to below 40°C, discharge the material, and seal and package to obtain a flexible polyisocyanate prepolymer resin.
[0109] The formula composition and preparation process of the flexible pressure-sensitive color-changing anticorrosive primer in this embodiment are as follows:
[0110] (1) Add 50 parts by weight of ethyl acetate solvent, 100 parts by weight of the above-obtained flexible polyisocyanate prepolymer resin, 40 parts by weight of Qingdao Baige 1500 mesh ultrafine talc, 35 parts by weight of α-phase nano-alumina (model HN-L100260) of Hengna New Materials Co., Ltd., 3.8 parts by weight of fumed silica SJ-301, 2.2 parts by weight of Levaslip466 leveling agent, 2.3 parts by weight of AFCONA2020 defoaming agent, and 3.8 parts by weight of BYK103 wetting and dispersing agent into a container in sequence, stir for 1.2 hours, grind and disperse with a sand mill until the fineness is ≤40 μm, then add 160 parts by weight of 7-diethylamino-3-[4'-(trifluoromethyl)benzoyl]methylcoumarin, stir at high speed in a closed manner for 0.8 hours, filter out the material, and seal and package to obtain component A; component A has a solid content of 65% and a fineness of 35 μm;
[0111] (2) 100 parts by weight of E402-90T flexible curing agent and 5.2 parts by weight of Jessica JSC-1120 adhesion promoter were stirred in a closed container for 0.5 h, the material was filtered out, and sealed and packaged to obtain component B;
[0112] (3) The component A and the component B prepared above were mixed in a weight ratio of A:B=80:12 to prepare a coating material. The coating thickness obtained after coating for performance testing was 40 to 60 μm.
[0113] The preparation method of the intelligent threaded fastener with visual tightening degree is as follows:
[0114] 1) A circle is cut around the center point of the bolt head end face of an external hexagonal aluminum alloy bolt (total length 3 cm, bolt head thickness 4 mm, bolt diameter 6 mm, hexagonal opposite side length 8 mm) to form an annular groove with a depth of 8 mm, a width of 1 mm, and an inner diameter of 2 mm. Then, the processed bolts and the matching nuts and gaskets are immersed in xylene for 5 hours, taken out and dried.
[0115] 2) First, the component A and the component B of the flexible pressure-sensitive color-changing anti-corrosion primer of the above-mentioned embodiment 2 are mixed according to the described usage ratio (80:12) to obtain the flexible pressure-sensitive color-changing anti-corrosion primer, and then the bolts, nuts and gaskets treated in step 1) are sprayed with the flexible pressure-sensitive color-changing anti-corrosion primer respectively, and the coating is made to fill the annular groove, and the coating is completely cured to obtain a smart threaded fastener with a visible tightness.
[0116] Example 3
[0117] The preparation method of the flexible polyisocyanate prepolymer resin in this embodiment comprises the following steps:
[0118] Step 1: Add 42 parts by weight of isophorone diisocyanate, 0.01 parts by weight of dioctyltin dilaurate, 12 parts by weight of ethyl acetate and 5 parts by weight of propylene glycol methyl ether acetate into a reaction kettle, introduce nitrogen protection, stir at 150 r / min at 25°C for 15 minutes to mix the materials evenly, then heat to 65°C and react for 20 minutes to obtain material 1.
[0119] Step 2: Add 0.10 parts by weight of Stabaxol-1 to material 1, heat to 78°C, slowly add 1.2 parts by weight of DMTDA under stirring at 180 r / min, and react at 85°C for 1.5 hours to obtain material 2.
[0120] Step 3: Slowly add 48 parts by weight of polyether polyol EP330N produced by Bluestar Dongda Chemical Co., Ltd. into material 2 at 78°C and stirring at 180 r / min, react at 85°C for 2.5 hours, then cool to 45°C to obtain material 3.
[0121] Step 4: Slowly add 0.01 parts by weight of benzoyl chloride to material 3 at 45°C and stirring at 150 r / min. After the addition, keep the reaction at 45°C for 1.5 hours. After the reaction is completed, add 12 parts by weight of ethyl acetate, cool to below 40°C, discharge the material, and seal and package to obtain a flexible polyisocyanate prepolymer resin.
[0122] The formula composition and preparation process of the flexible pressure-sensitive color-changing anticorrosive primer in this embodiment are as follows:
[0123] (1) Add 20 parts by weight of butyl acetate solvent and 20 parts by weight of propylene glycol methyl ether acetate solvent, 100 parts by weight of the above-obtained flexible polyisocyanate prepolymer resin, 38 parts by weight of Guangxi Guihua 1250 mesh ultrafine talc powder, 40 parts by weight of α-phase nano-alumina (model PAT-05A) of Baoket New Materials Co., Ltd., 3.2 parts by weight of fumed silica HB-151, 2.6 parts by weight of BYK-378 leveling agent, 2.5 parts by weight of AFCONA2020 defoamer, and 3.4 parts by weight of RD9125 wetting and dispersing agent in a container, stir for 1 hour, grind and disperse with a sand mill until the fineness is ≤40 μm, then add 160 parts by weight of 7-diethylamino-3-[4'-(trifluoromethyl)benzoyl]methylcoumarin, stir at high speed in a closed manner for 0.5 hour, filter the material, and seal and package to obtain component A; component A has a solid content of 63% and a fineness of 35 μm;
[0124] (2) 100 parts by weight of GB805A-100 flexible curing agent and 4.5 parts by weight of Jessica JSC-1120 adhesion promoter were stirred in a closed container for 0.5 h, the material was filtered out, and sealed and packaged to obtain component B;
[0125] (3) The component A and the component B prepared above were mixed in a weight ratio of A:B=80:14 to prepare a coating material. The coating thickness obtained after coating for performance testing was 40 to 60 μm.
[0126] The preparation method of the intelligent threaded fastener with visual tightening degree is as follows:
[0127] 1) A circle is cut around the center point of the bolt head end face of an external hexagonal aluminum alloy bolt (total length 3 cm, bolt head thickness 4 mm, bolt diameter 6 mm, hexagonal opposite side length 8 mm) to form an annular groove with a depth of 8 mm, a width of 1 mm, and an inner diameter of 2 mm. Then, the processed bolts and the matching nuts and gaskets are immersed in xylene for 5 hours, taken out and dried.
[0128] 2) First, the component A and the component B of the flexible pressure-sensitive color-changing anti-corrosion primer of the above-mentioned embodiment 3 are mixed according to the described usage ratio (80:14) to obtain the flexible pressure-sensitive color-changing anti-corrosion primer, and then the bolts, nuts and gaskets treated in step 1) are sprayed with the flexible pressure-sensitive color-changing anti-corrosion primer respectively, and the coating is made to fill the annular groove, and the coating is completely cured to obtain a smart threaded fastener with a visible tightness.
[0129] Comparative Example 1
[0130] The preparation method of the flexible polyisocyanate prepolymer resin in this comparative example is the same as that in Example 1.
[0131] The formula composition and preparation process of the primer in this comparative example are as follows:
[0132] (1) Add 45 parts by weight of butyl acetate solvent, 100 parts by weight of the above-obtained flexible polyisocyanate prepolymer resin, 35 parts by weight of Guangxi Guihua 1250 mesh ultrafine talc powder, 40 parts by weight of α-phase nano-alumina (model PAT-05A) from Baoket New Materials Co., Ltd., 3.5 parts by weight of fumed silica SJ-301, 2.5 parts by weight of BYK-378 leveling agent, 2.5 parts by weight of BYK065 defoamer, and 3.5 parts by weight of AFCONA4015 wetting and dispersing agent into a container in sequence, stir for 1 hour, grind and disperse with a sand mill until the fineness is ≤40μm, then add 150 parts by weight of titanium dioxide, stir at high speed in a closed manner for 0.5h, filter out the material, and seal and package to obtain component A. The solid content of component A is 63% and the fineness is 35μm;
[0133] (2) In a container, 100 parts by weight of GB805A-100 flexible curing agent and 5.5 parts by weight of Deqian 1121 adhesion promoter were stirred for 0.5 h, filtered, and sealed to obtain component B;
[0134] (3) The component A and the component B prepared above were mixed in a weight ratio of A:B=80:10 to prepare a coating material. The coating thickness obtained after coating for performance testing was 40 to 60 μm.
[0135] The preparation method of the threaded fastener of this comparative example is as follows:
[0136] 1) A circle is cut around the center point of the bolt head end face of an external hexagonal aluminum alloy bolt (total length 3 cm, bolt head thickness 4 mm, bolt diameter 6 mm, hexagonal opposite side length 8 mm) to form an annular groove with a depth of 8 mm, a width of 1 mm, and an inner diameter of 2 mm. Then, the processed bolts and the matching nuts and gaskets are immersed in xylene for 5 hours, taken out and dried.
[0137] 2) First, the above-mentioned component A and component B are mixed according to the usage ratio (80:10) to obtain a primer, and then the bolts, nuts and washers treated in step 1) are sprayed with the primer respectively, and the coating fills the annular groove, and the coating is completely cured to obtain a threaded fastener coated with the primer.
[0138] Comparative Example 2
[0139] The preparation method of the flexible polyisocyanate prepolymer resin in this comparative example is the same as that in Example 3.
[0140] The formula composition and preparation process of the primer in this comparative example are as follows:
[0141] (1) Add 20 parts by weight of butyl acetate solvent and 20 parts by weight of propylene glycol methyl ether acetate solvent, 100 parts by weight of flexible polyisocyanate prepolymer resin, 38 parts by weight of Guangxi Guihua 1250 mesh ultrafine talc powder, 40 parts by weight of α-phase nano-alumina (model PAT-05A) of Baoket New Materials Co., Ltd., 3.2 parts by weight of fumed silica HB-151, 2.6 parts by weight of BYK-378 leveling agent, 2.5 parts by weight of AFCONA2020 defoamer, and 3.4 parts by weight of RD9125 wetting and dispersing agent in a container, stir for 1 hour, grind and disperse with a sand mill until the fineness is ≤40 μm, then add 160 parts by weight of 7-diethylamino-3-[4'-(trifluoromethyl)benzoyl]methylcoumarin, stir at high speed in a closed manner for 0.5 hour, filter the material, and seal and package to obtain component A; component A has a solid content of 63% and a fineness of 35 μm;
[0142] (2) 100 parts by weight of GB805A-100 flexible curing agent was sealed and stirred in a container for 0.5 h, the material was filtered out, and sealed and packaged to obtain component B;
[0143] (3) The component A and the component B prepared above were mixed in a weight ratio of A:B=80:14 to prepare a coating material. The coating thickness obtained after coating for performance testing was 40 to 60 μm.
[0144] The preparation method of the threaded fastener of this comparative example is as follows:
[0145] 1) A circle is cut around the center point of the bolt head end face of an external hexagonal aluminum alloy bolt (total length 3 cm, bolt head thickness 4 mm, bolt diameter 6 mm, hexagonal opposite side length 8 mm) to form an annular groove with a depth of 8 mm, a width of 1 mm, and an inner diameter of 2 mm. Then, the processed bolts and the matching nuts and gaskets are immersed in xylene for 5 hours, taken out and dried.
[0146] 2) First, the above-mentioned component A and component B are mixed in the amount ratio (80:14) to obtain a primer, and then the bolts, nuts and washers treated in step 1) are sprayed with the primer respectively, and the coating fills the annular groove, and is completely cured to obtain a threaded fastener coated with the primer.
[0147] Comparative Example 3
[0148] The preparation method of the flexible polyisocyanate prepolymer resin in this comparative example is the same as that in Example 3.
[0149] The formula composition and preparation process of the flexible pressure-sensitive color-changing anticorrosive primer in this comparative example are as follows:
[0150] (1) Add 20 parts by weight of butyl acetate solvent and 20 parts by weight of propylene glycol methyl ether acetate solvent, 100 parts by weight of flexible polyisocyanate prepolymer resin, 78 parts by weight of Guangxi osmanthus 1250 mesh ultrafine talc powder, 3.2 parts by weight of fumed silica HB-151, 2.6 parts by weight of BYK-378 leveling agent, 2.5 parts by weight of AFCONA2020 defoamer, and 3.4 parts by weight of RD9125 wetting and dispersing agent in a container, stir for 1 hour, grind and disperse with a sand mill until the fineness is ≤40 μm, then add 160 parts by weight of 7-diethylamino-3-[4'-(trifluoromethyl)benzoyl]methylcoumarin, stir at high speed in a closed manner for 0.5 hour, filter the material, and seal and package to obtain component A; component A has a solid content of 63% and a fineness of 35 μm;
[0151] (2) 100 parts by weight of GB805A-100 flexible curing agent and 4.5 parts by weight of Jessica JSC-1120 adhesion promoter were stirred in a closed container for 0.5 h, the material was filtered out, and sealed and packaged to obtain component B;
[0152] (3) The component A and the component B prepared above were mixed in a weight ratio of A:B=80:14 to prepare a coating material. The coating thickness obtained after coating for performance testing was 40 to 60 μm.
[0153] The preparation method of the threaded fastener of this comparative example is as follows:
[0154] 1) A circle is cut around the center point of the bolt head end face of an external hexagonal aluminum alloy bolt (total length 3 cm, bolt head thickness 4 mm, bolt diameter 6 mm, hexagonal opposite side length 8 mm) to form an annular groove with a depth of 8 mm, a width of 1 mm, and an inner diameter of 2 mm. Then, the processed bolts and the matching nuts and gaskets are immersed in xylene for 5 hours, taken out and dried.
[0155] 2) First, the above-mentioned component A and component B are mixed according to the usage ratio (80:14) to obtain a primer, and then the bolts, nuts and washers treated in step 1) are sprayed with the primer respectively, and the coating fills the annular groove, and the coating is completely cured to obtain a threaded fastener coated with the primer.
[0156] Comparative Example 4
[0157] The preparation method of the flexible polyisocyanate prepolymer resin in this comparative example is the same as that in Example 3.
[0158] The formula composition and preparation process of the flexible pressure-sensitive color-changing anticorrosive primer in this comparative example are as follows:
[0159] (1) Add 20 parts by weight of butyl acetate solvent and 20 parts by weight of propylene glycol methyl ether acetate solvent, 100 parts by weight of the above-obtained flexible polyisocyanate prepolymer resin, 78 parts by weight of α-phase nano-alumina (model PAT-05A) of Paket New Materials Co., Ltd., 3.2 parts by weight of fumed silica HB-151, 2.6 parts by weight of BYK-378 leveling agent, 2.5 parts by weight of AFCONA2020 defoamer, and 3.4 parts by weight of RD9125 wetting and dispersing agent into a container in sequence, stir for 1 hour, grind and disperse with a sand mill until the fineness is ≤40 μm, then add 160 parts by weight of 7-diethylamino-3-[4'-(trifluoromethyl)benzoyl]methylcoumarin, stir at high speed in a closed manner for 0.5 hour, filter out the material, and seal and package to obtain component A; component A has a solid content of 63% and a fineness of 35 μm;
[0160] (2) 100 parts by weight of GB805A-100 flexible curing agent and 4.5 parts by weight of Jessica JSC-1120 adhesion promoter were stirred in a closed container for 0.5 h, the material was filtered out, and sealed and packaged to obtain component B;
[0161] (3) The component A and the component B prepared above were mixed in a weight ratio of A:B=80:14 to prepare a coating material. The coating thickness obtained after coating for performance testing was 40 to 60 μm.
[0162] The preparation method of the threaded fastener of this comparative example is as follows:
[0163] 1) A circle is cut around the center point of the bolt head end face of an external hexagonal aluminum alloy bolt (total length 3 cm, bolt head thickness 4 mm, bolt diameter 6 mm, hexagonal opposite side length 8 mm) to form an annular groove with a depth of 8 mm, a width of 1 mm, and an inner diameter of 2 mm. Then, the processed bolts and the matching nuts and gaskets are immersed in xylene for 5 hours, taken out and dried.
[0164] 2) First, the above-mentioned component A and component B are mixed in the amount ratio (80:14) to obtain a primer, and then the bolts, nuts and washers treated in step 1) are sprayed with the primer respectively, and the coating fills the annular groove, and is completely cured to obtain a threaded fastener coated with the primer.
[0165] Table 1. Main performance indicators of the flexible pressure-sensitive color-changing anticorrosive primers prepared in Examples 1 to 3 and Comparative Examples 1 to 4
[0166]
[0167]
[0168] It can be seen from the above table that the coatings of Examples 1 to 3 all have good tensile strength and elongation at break, good tear strength, good bending resistance, and have excellent environmental adaptability such as excellent neutral salt spray resistance, good acid salt spray resistance, and excellent moisture and heat resistance. In particular, through the neutral salt spray test using the "×" method, it can be seen that the flexible pressure-sensitive color-changing anti-corrosion primer of the present invention has good anti-corrosion performance, and the paint film has a smooth appearance, no bubbles, and no particles. The intelligent threaded fasteners can achieve tightening color change, and can provide a certain indication of the tightening degree of the bolts. Compared with Comparative Example 1, Examples 1 to 3 have no significant difference in tensile strength, elongation at break, bending resistance, acid salt spray resistance, neutral salt spray resistance, etc., but the tightening bolts of Comparative Example 1 will not indicate; Compared with Comparative Example 2, Examples 1 to 3 have no significant difference in other properties, but since Comparative Example 2 does not add adhesion promoter, Comparative Example 2 is inferior to Examples 1 to 3 in adhesion, water resistance, bending resistance, neutral salt spray resistance, acid salt spray resistance, and wet heat resistance; Compared with Comparative Example 3, Example 3 has no significant difference in other properties, but since Comparative Example 3 does not add nano aluminum oxide, the pencil hardness can only reach HB level. Compared with Comparative Example 4, Example 3 has no significant difference in other properties, but since Comparative Example 4 does not add ultrafine talcum powder, the pencil hardness can only reach H level. In summary, the flexible pressure-sensitive color-changing anti-corrosion primer of the present invention can exhibit good tensile strength and elongation at break, good tear strength, good bending resistance, and excellent environmental adaptability such as resistance to neutral salt spray, good resistance to acidic salt spray, and excellent resistance to moisture and heat; the present invention enables the coating system to have a higher pencil hardness index through the synergistic effect of ultrafine talcum powder and nano-aluminum oxide.
Claims
1. A flexible pressure-sensitive color-changing anti-corrosion primer, comprising component A and component B; the component A comprises a flexible resin, a pressure-induced color-changing indicator, ultrafine talcum powder, nano-aluminum trioxide and a wetting dispersant; the component B comprises a flexible curing agent and an adhesion promoter; the pressure-induced color-changing indicator is 7-diethylamino-3-[4'-(trifluoromethyl)benzoyl]methylcoumarin; the flexible resin is selected from at least one of a flexible epoxy-modified acrylic resin and a flexible polyisocyanate prepolymer resin; Each component in the A component is calculated based on 100 parts by weight of the flexible resin. 100-180 parts by weight of a piezochromic indicator; 20-80 parts by weight of superfine talc; 30-80 parts by weight of nano-aluminum oxide; 2 to 5 parts by weight of wetting and dispersing agent; The components in the B component are calculated based on 100 parts by weight of the flexible curing agent. Adhesion promoter 0-10 parts by weight; The dosage ratio of component A to component B is (4-12):
1.
2. The flexible pressure-sensitive color-changing anticorrosive primer according to claim 1, characterized in that: Each component in the A component is calculated based on 100 parts by weight of the flexible resin. 120-170 parts by weight of a piezochromic indicator; 30-50 parts by weight of superfine talc; 30-50 parts by weight of nano-aluminum oxide; 2 to 4 parts by weight of wetting and dispersing agent; The components in the B component are calculated based on 100 parts by weight of the flexible curing agent. 2 to 10 parts by weight of adhesion promoter; The dosage ratio of component A to component B is (4-10):
1.
3. The flexible pressure-sensitive color-changing anticorrosive primer according to claim 1, characterized in that: The preparation method of the flexible polyisocyanate prepolymer resin comprises the following steps: Step 1: reacting isocyanate, catalyst and part of solvent A to obtain material 1; Step 2: Add a stabilizer and a cross-linking agent to material 1 to react to obtain material 2; Step 3: Adding oligomer polyol to material 2 to react to obtain material 3; Step 4: adding an anticoagulant to material 3 to react, and after the reaction is completed, adding the remaining solvent A to obtain a flexible polyisocyanate prepolymer resin.
4. The flexible pressure-sensitive color-changing anticorrosive primer according to claim 3, characterized in that: The isocyanate is selected from one or more of isophorone diisocyanate, hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, and p-phenylene diisocyanate; and / or, The catalyst is selected from one or more of triethylamine and dioctyltin dilaurate; and / or, The oligomer polyol is selected from one or more of polycaprolactone diol, polyether polyol and polybutadiene polyol; and / or, The anticoagulant is selected from one or more of benzoyl chloride and phosphoric acid; and / or, The solvent A is selected from one or more of butyl acetate, ethyl acetate, and propylene glycol methyl ether acetate.
5. The flexible pressure-sensitive color-changing anticorrosive primer according to claim 4, characterized in that: The isocyanate is selected from isophorone diisocyanate and / or p-phenylene diisocyanate.
6. The flexible pressure-sensitive color-changing anticorrosive primer according to claim 1, characterized in that: The ultrafine talc powder has a fineness of 500 to 2000 mesh; and / or, The particle size of the nano aluminum oxide is 5 to 500 nm.
7. The flexible pressure-sensitive color-changing anticorrosive primer according to claim 1, characterized in that: The ultrafine talc powder has a fineness of 1250-2000 mesh; and / or, The particle size of the nano aluminum oxide is 10 to 100 nm.
8. The flexible pressure-sensitive color-changing anticorrosive primer according to any one of claims 1 to 7, characterized in that: The component A also includes any one of fumed silica, a leveling agent, a defoaming agent, and a solvent B.
9. A method for preparing the flexible pressure-sensitive color-changing anticorrosive primer according to any one of claims 1 to 8, comprising: Firstly, component A and component B are mixed separately, and then component A and component B are mixed to obtain the flexible pressure-sensitive color-changing anticorrosive primer.
10. Application of a flexible pressure-sensitive color-changing anti-corrosion primer prepared by the preparation method of the flexible pressure-sensitive color-changing anti-corrosion primer as described in any one of claims 1 to 8 or the flexible pressure-sensitive color-changing anti-corrosion primer as described in claim 9 in threaded fasteners, rivets, joints and fatigue-critical parts.
11. An intelligent threaded fastener with visible tightening degree, the fastener is a screw, or includes a bolt and a nut and optionally a gasket, the outer layer of the screw or bolt is coated with the flexible pressure-sensitive color-changing anti-corrosion primer described in any one of claims 1 to 8 or the flexible pressure-sensitive color-changing anti-corrosion primer prepared by the preparation method of the flexible pressure-sensitive color-changing anti-corrosion primer described in claim 9.
12. The intelligent threaded fastener with visual tightening degree as claimed in claim 11, characterized in that: The bolt comprises a bolt head and a bolt column, wherein the bolt head is located at the upper part of the bolt column, an annular groove is arranged on the end surface of the bolt head, and the center of the annular groove is located on the axis of the bolt column.
13. The intelligent threaded fastener with visual tightening degree as claimed in claim 12, characterized in that: The annular groove extends deep into the bolt column; and / or, the width of the annular groove is 1-2 mm; and / or, The annular groove is filled with a coating of the flexible pressure-sensitive color-changing anti-corrosion primer.
14. The intelligent threaded fastener with visible tightening degree as claimed in claim 13, characterized in that: The depth of the annular groove penetrating into the bolt column part is 1 / 8 to 1 / 4 of the length of the bolt column.
15. The intelligent threaded fastener with visible tightening degree as claimed in claim 11, characterized in that: The screw comprises a screw head and a screw rod, wherein the screw head is located at the upper part of the screw rod, an annular groove is arranged on the end surface of the screw head, and the center of the annular groove is located on the axis of the screw rod.
16. The intelligent threaded fastener with visual tightening degree as claimed in claim 15, characterized in that: The annular groove extends deep into the screw portion; and / or, the width of the annular groove is 1 to 2 mm; and / or, The annular groove is filled with a coating of the flexible pressure-sensitive color-changing anti-corrosion primer.
17. The intelligent threaded fastener with visual tightening degree as claimed in claim 16, characterized in that: The depth of the annular groove penetrating into the screw portion is 1 / 8 to 1 / 4 of the length of the screw.
Citation Information
Patent Citations
Self-tapping screw
CN108587402A
Acrylic acid flexible anticorrosive primer and preparation method thereof
CN112680078A
Aggregation-induced emission type piezochromic coating and preparation method thereof
CN116004060A
Urethane prepolymer composition and a polyurethane coating composition system
US4929667A